Temperature and pH dual stimuli responsive PCL- b -PNIPAAm block copolymer assemblies and the cargo release studies - Patil, Sachin S.; Wadgaonkar, Prakash (Journal of Polymer Science Part A Polymer Chemistry, 2017)
A new atom transfer radical polymerization (ATRP) initiator, namely, 2-(1-(2-azidoethoxy)ethoxy)ethyl 2-bromo-2-methylpropanoate containing both “cleavable” acetal linkage and “clickable” azido group was synthesized. Well-defined azido-terminated poly(N-isopropylacrylamide)s (PNIPAAm-N3)s with molecular weights and dispersity in the range 11,000–19,000 g mol−1 and 1.20–1.28, respectively, were synthesized employing the initiator by ATRP. Acetal containing PCL-b-PNIPAAm block copolymer was obtained by alkyne–azide click reaction of azido-terminated PNIPAAm-N3 with propargyl-terminated PCL. Critical aggregation concentration (CAC) of PCL-b-PNIPAAm copolymer in aqueous solution was found to be 8.99 × 10−6 M. Lower critical solution temperature (LCST) of PCL-b-PNIPAAm copolymer was found to be 32 °C which was lower than that of the precursor PNIPAAm-N3 (36.4 °C). The effect of dual stimuli viz. temperature and pH on size and morphology of the assemblies of PCL-b-PNIPAAm block copolymer revealed that the copolymer below LCST assembled in spherical micelles which subsequently transformed to unstable vesicles above the LCST. Heating these assemblies above 40 °C led to the precipitation of PCL-b-PNIPAAm block copolymer. Whereas, at decreased pH, micelles of PCL-b-PNIPAAm copolymer disintegrate due to the cleavage of acetal linkage and precipitation of hydrophobic hydroxyl-terminated PCL. The encapsulated pyrene release kinetics from the micelles of synthesized PCL-b-PNIPAAm copolymer was found to be faster at higher temperature and at lower pH. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017